SISTEM PRESENSI SISWA MENGGUNAKAN QR CODE DAN NOTIFIKASI WHATSAPP DI SMP TPN SENDANG BIRU - Fanny Eka Safira; Purwanto, Hari Lugis; Syahminan (JOURNAL OF INFORMATION TECHNOLOGY, INFORMATION SYSTEMS AND COMMUNICATIONS, 2025)
Abstract. The school attendance system is the process of recording attendance during teaching and learning activities. Every school has an attendance system, including SMP Taman Petani dan Nelayan (TPN) Sendang Biru. At SMP TPN Sendang Biru, the student attendance system currently uses a manual method, where names are called one by one at the beginning of each class. This method is prone to errors and allows students to skip classes unnoticed. To address this issue, a QR Code-based attendance system with WhatsApp notifications is proposed. At the beginning of each lesson, students scan a QR Code generated by the teacher, and their attendance data is automatically recorded while simultaneously sending a real-time notification to parents. This system is expected to streamline the attendance process and improve student attendance monitoring at SMP TPN Sendang Biru.The objective of this study is to develop a Web-Based Student Attendance Information System Using QR Code and WhatsApp Notifications at SMP TPN Sendang Biru. This system is developed using the waterfall model, which consists of five main stages: requirement analysis, system design, coding, program testing, and implementation.The research results in an application the Student Attendance Information System, which can effectively monitor student attendance at school. The User Acceptance Test (UAT) results, with an average overall score of 84.73%, indicate that the designed system successfully supports attendance management at SMP TPN Sendang Biru.